UNESCO, cultural heritage, and outstanding universal value : value-based analyses of the World Heritage and Intangible Cultural Heritage Conventions - Labadi, Sophia (Archaeology in society series, 2013)
This book explores the international legal framework developed by UNESCO to identify and protect world heritage and its implementation at the national level. Drawing on close policy analysis of UNESCO's major documents, extensive professional experience at UNESCO, as well as in-depth analyses of case studies from Asia, Europe, and Latin America, Sophia Labadi offers a nuanced discussion of the constitutive role of national understandings of a universalist framework. The discussion departs from considerations of the World Heritage Convention as Eurocentric and offers a more complex analysis of how official narratives relating to non-European and non-traditional heritage mark a subversion of a dominant and canonical European representation of heritage. It engages simultaneously with a diversity of discourses across the humanities and social sciences and with related theories pertaining not only to tangible and intangible heritage, conservation, and archaeology but also political science, social theory, tourism and development studies, economics, cultural, and gender studies. In doing so, it provides a critical review of many key concepts, including tourism, development, sustainability, intangible heritage, and authenticity.
Keywords: Unesco; Convention for the Safeguarding of the Intangible Cultural Heritage : (2003 October 17); World Heritage Convention : (1972 November 16); Cultural property : Protection (International law); aineeton kulttuuriperintö; aitous; kulttuuriperintö; lainsäädäntö; maailmanperintökohteet; suojelukohteet; immateriellt kulturarv; äkthet; kulturarv; lagstiftning; världsarvsobjekt; skyddsobjekt